A Sinister Disease Hides Behind Recalcitrant Mucocutaneous Disorder - Harihar Adhikari; Deeptara Pathak Thapa; Priya Bhusal (Nepal Journal of Dermatology, Venereology & Leprology)
Paraneoplastic pemphigus (PNP) is a rare autoimmune disorder associated with underlying benign or malignant neoplasia. Its signs and symptoms may be the first presentation of a concealed malignancy. Due to late diagnosis, prognosis of PNP is not good, so early diagnosis and treatment is of paramount importance. We present a case of 22 years old female who presented to our out patient department (OPD) with history of recurrent, severe, recalcitrant, painful oral ulcers; lichenoid lesions over the hands and feet and widespread blistering and erosions involving the soles. Histopathological examination was consistent with paraneoplastic pemphigus and showed features of lichenoid dermatitis. CT scan revealed retroperitoneal mass suggestive of Castleman disease. The patient was referred to surgical team for further management.